2023
DOI: 10.1016/j.fshw.2023.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Tea Ingestion to Salivary Redox and Flow Rate in Healthy Subjects

Abstract: The biochemistry of human saliva can be altered by food intake. The benefits of tea drinking were extensively studied but the influence of tea ingestion on human saliva has not been revealed. The work aimed to investigate the immediate and delayed effect of vine tea, oolong tea and black tea intake on certain salivary biochemistry and fl ow rate. The saliva samples of healthy subjects were collected before, after and 30 min after tea ingestion. The chemical compositions and antioxidant capacity of tea samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
(50 reference statements)
2
5
0
Order By: Relevance
“…Both hot water (58 °C, 200 mL) and cold water (7 °C, 200 mL) significantly increased salivary uric acid levels ( p < 0.05) 30 min after the water ingestion. The results were in line with the previous studies reported by Chong et al 24 . The salivary UA level in this study remained in the normal range of healthy adults.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Both hot water (58 °C, 200 mL) and cold water (7 °C, 200 mL) significantly increased salivary uric acid levels ( p < 0.05) 30 min after the water ingestion. The results were in line with the previous studies reported by Chong et al 24 . The salivary UA level in this study remained in the normal range of healthy adults.…”
Section: Resultssupporting
confidence: 94%
“…Sun et al found that the black tea polysaccharide significantly mitigated the CCl 4 -induced increase in liver MDA in mice 60 . As reported previously, the same kind of black tea increased the salivary MDA 15 , while the oolong tea and vine tea took longer time (30 min) to raise the salivary MDA level 24 . The MDA increments caused by the tea ingestion is temporary and well below the pathological increments.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations